Follow-up of the survivors of congenital diaphragmatic hernia - Pinto, Jorge Correia (2012)
INTRODUCTION: Survivors of congenital diaphragmatic hernia have increased with the introduction of new treatment modalities and have been reported to experience ongoing medical morbidity until adulthood. AIM: To describe the long-term functional impact of congenital diaphragmatic repair on the survivors of a single institution cohort of newborns over a 14-year period. METHODS: The follow up medical charts of 39 congenital diaphragmatic hernia survivors treated at a tertiary neonatal intensive care unit, from January 1997 to December 2010, were analyzed. RESULTS: The median age at follow up was 70 (4-162) months. Gastrointestinal sequelae were the most common with 12 (30.7%) patients affected by failure to thrive. Chronic lung disease occurred in 5 (12.8%) patients, neurodevelopmental delay in 5 (12.8%), musculoskeletal sequelae in 6 (15.3%), recurrence of hernia in 4 (10.2%) and 2 (7.6%) were deceased. CONCLUSION: Congenital diaphragmatic hernia survivors are a group of patients that requires long term periodic follow up in a multidisciplinary setting to provide adequate support and improve their quality of life.